Preserving and Promoting the Herbarium of the University of Milan through Digital Technologies. Issue 1 (November 2020) - Barat`e, Adriano; Caccianiga, Marco; Caporali, Elisabetta; Ludovico, Luca A.; Pinto, Silvia; Presti, Giorgio; Sala, Enrico; Testa, Antonella
Abstract: This paper deals with the application of digital technologies to the preservation and exploitation of the heterogeneous documents of the Herbarium Universitatis Mediolanensis of the University of Milan. The collection, dating back to the 19 th and 20 th Century, is mainly constituted by exsiccata, i.e. specimens (whole plants or plant parts) in dried form mounted on paper sheets; the archive also includes large botanical lithographs originally used in schools as educational tools. The long-term goal of the project is to complete the digitization campaign and make all these documents publicly available via a Web portal; currently, all metadata (23000 files approx.) and about 6000 digital objects are online. In this work, the whole process will be discussed, from digitization to the implementation of the Web portal based on a multimedia relational database.